Late Pleistocene-Holocene history of Svalbard ice caps and glaciers – integrating marine, terrestrial and lacustrine archives - Allaart, Lis (UiT Norges arktiske universitet, 2021)
The Arctic regions are affected by the modern climate change to a greater extent than the global average. This effect is called the Arctic amplification and is reflected in air temperatures rising with double rate and increased precipitation compared to the global average. The climate of Svalbard is strongly related to variations in the atmospheric and oceanic circulation patterns, and the archipelago is, therefore, ideal location to study the climate sensitivity of the Arctic. This dissertation presents research on the Late Pleistocene and Holocene glacial history of Svalbard. Marine, lacustrine and terrestrial archives are assessed in a confined geographical area in northern Wijdefjorden, northern Spitsbergen, and the regional timing of the deglaciation, Holocene Thermal Maximum, Holocene Glacial Minimum as well as the onset of the Neoglacial are identified (Papers I-III). The research focus is on Wijdefjorden, Femmilsjøen and the NW part of the Åsgardfonna ice cap. The results are placed in a regional context and compared to studies across Svalbard. A review of the Holocene glacial history of Svalbard is presented in Paper IV, where all Holocene chronological data from Svalbard are re-calibrated or calculated and gathered in one database. The landforms in the fjord (Paper I) and the lowermost acoustic and sedimentary facies (Papers I-II) are interpreted to be indicative of grounded, warm-based ice occupied the fjord during the Last Glacial. By contrast, Paper III speculates that parts of the terrestrial terrain are similar to forelands of cold-based glaciers in Antarctica, which may have been covered by cold-based and little erosive glacier ice during the Last Glacial. Among the findings are that northern Svalbard deglaciated early. Wijdefjorden is inferred to deglaciate at least prior to 12.4 ± 0.3 cal. ka BP and potentially prior to 14.5 ± 0.3 cal. ka BP. Femmilsjøen deglaciated potentially prior to 16.1 ± 0.3 cal. ka BP. Deglaciation occurred in a stepwise manner and was characterised by fluctuating water ...